An Internal Focus Leads to Longer Quiet Eye Durations in Novice Dart Players - Querfurth, Sydney; Schücker, Linda; de Lussanet, Marc H. E.; Zentgraf, Karen (Frontiers in Psychology, 2016)
While the benefits of both an external focus of attention and of a longer quiet eye duration have been well researched in a wide range of sporting activities, little is known about the interaction of these two phenomena and how a potential interaction might influence performance. It was this study’s aim to investigate the interaction and potential effect on performance by using typical focus of attention instructions in a dart throwing task and examining both the quiet eye and performance outcome. The results replicate neither the benefit of an external focus of attention nor the benefit of a longer quiet eye duration. However, an interaction was observed, as quiet eye was prolonged by an earlier onset and later offset in the internal focus condition only. As the typical effect of a performance benefit due to an external focus could not be replicated, the interaction must be interpreted with caution. The results are discussed and interpreted in light of the inhibition hypothesis and possible avenues for future research are suggested.